Incidence of cesarean section and analysis of risk factors for failed conversion of labor epidural to surgical anesthesia: A prospective, observational study in a tertiary care center - Samina Ismail; Shakaib Chugtai; Alia Hussain (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: This study aimed to analyze the effect of labor epidural (LE) on the incidence of cesarean section (CS) and assess the risk factors involved in failed conversion of LE to surgical anesthesia for CS. Material and Methods: A prospective observational study of 18 months from January 2012 to June 2013 was conducted on all patients who had delivered in the labor room suit of our hospital. The data collected for all 4694 patients included their demographics, parity and mode of delivery. In addition a predesigned proforma, with additional information was used for 629 parturient with LE. Results: During the study period, total numbers of deliveries performed in our hospital were 4694, with an epidural rate of 13.4% (629/4694). No significant difference (P = 0.06) was observed in the rate of CS among women with or without LE (28 % [n = 176/629] vs. 31.7 % [n = 1289/4065]), however, a statistically significant difference (P < 0.01) was observed in the rate of assisted delivery in patients receiving LE as compared to those delivering without it (8.7% [n = 55/629] vs. n = 3.7% [154/4065]). For 176 patients requiring CS, LE utilization for surgical anesthesia was 52.8% (93/176) and factors identified for not utilizing LE in 47% (83/176) were; failure to achieve surgical anesthesia in 6.8% (12/176), emergency CS in 28.4% (50/176), patient preference in 6.8% (12/176) and inadequate labor pain relief with LE in 5.1% (9/176) patients. Non-obstetric anesthesiologists were involved in 59% (49/83) of cases where LE was not used for CS. Conclusion: LE had no effect on the rate of CS; however it significantly increased (P < 0.01) the rate of assisted delivery. Factors like inadequate LE, emergency situations and non-obstetric anesthesiologists can all be responsible for failed conversion of LE to surgical anesthesia for CS.